A Discourse Analysis Of Advertisements Of Fashion In Clothing In English And Vietnamese - Trịnh Thị Minh Trang (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study aims at conducting a discourse analysis of advertisements of fashion in clothing in English and in Vietnamese. The data for analysis in this thesis are 300 samples of advertisements of fashion in clothing (150 in English and 150 in Vietnamese) collected from fashion websites in the United States and Vietnam. The study is carried out based on the theories of discourse analysis and a combination of a variety of methods such as descriptive, comparative, contrastive, analytic and inductive. The study focus on analyzing some typical discourse features in order to point out the similarities and differences between advertisements of fashion in clothing in English and Vietnamese in terms of their layout, lexical feature, grammatical feature and cohesive devices. The findings of this study are clearly presented based on a survey of 150 English advertisements of fashion in clothing and 150 advertisements of fashion in clothing in Vietnamese. Hopefully, the results of the study will really provide some practical applications for teaching and learning English. This study may also be useful for those who are interested in advertising, especially advertisements of fashion in clothing.